Analisis Framing Pemberitaan Kontroversial Campaign Zara “The Jacket” Singgung Korban Gaza Pada BBC News & Suara.com - Afni Tiana Rosa; Andri Prasetyo Yuwono (Jurnal Ilmu Komunikasi dan Bisnis, 2024)
This research focuses on how online media presented the news of the controversial case of the ZARA Atelier "The Jacket" campaign which was considered offensive to Gaza victims on two national online media Suara.com and BBC News International media. This study aims to understand how BBC News and Suara.com media construct news on the reality that occurs and see how the event is highlighted or omitted. The research method uses a descriptive qualitative method with a constructivism paradigm approach as a basis for knowing the views of each individual in constructing news with different backgrounds. This research uses Robert N. Entman's framing analysis model which sees framing in two dimensions: issue selection and emphasis on certain aspects. The results showed that BBC News and Suara.com online media in packaging information into news, have news similarities but package them with different styles and perspectives regarding the ZARA Atelier "The Jacket" campaign case. BBC News in framing or packaging news is in accordance with what happened, however, it tends to focus a little on ZARA's perspective, as evidenced by the emphasis on the news content. Meanwhile, Suara.com in framing focuses on public opinion, as evidenced by the emphasis on the aspects of writing facts, and other emphases, which show support for the boycott.